MASSAGE COUNTER PRESSURE AND MASSAGE EFFLEURAGE EFFECTIVELY REDUCE LABOR PAIN - Matilda Paseno; Rosmina Situngkir; Heny Pongantung; Febriana Wulandari; Desi Astria (POLITEKNIK KESEHATAN KEMENTERIAN KESEHATAN MANADO, 2019)
Background: Untreated pain can cause death in both mother and baby because pain can cause breathing and the mother's heart rate to increase which causes blood flow and oxygen to the placenta to be disrupted. Counterpressure massage which is a strong pressure massage by putting the heel of the hand or a flat part of the hand, or also using a tennis ball. Aims: of this study was to determine the differences in the effectiveness of counterpressure massage with massage effleurage against first stage labor pain in the Special Hospital of the Mother and Child Pertiwi Makassar area. Method: This study uses a Quasi Experiment research method with a pre-test post-test control design approach. The sample selection is done by consecutive sampling technique, the number of samples is 20 respondents (10 respondents for counterpressure massage and 10 respondents for massage effleurage). Data were processed using the Mann-Whitney test. Results: From the data analysis, the results obtained p-value = 0.009. Discussion: This shows that the value of p <α, then the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. Conclusion: counterpressure massage is more effective than massage effleurage to reduce labor pain in the first stage.